Effervescent Powder Formulation of Ethanol Extract of African Leaves (Vernonia amygdalina) as an α-amylaseInhibitor - Norainny Yunitasari; Nasyanka, Anindi Lupita; Luthfi, Sania Al; Ramadhanti, Nadya; Zulfiyana, Lindah Isna (Sainteknol : Jurnal Sains dan Teknologi, 2024)
Vernonia amygdalina or African leaves are reported to have many biological activities, including antidiabetic. However, there are still many people who have not used this plant as an antidiabetic treatment. This research aims to create a medicinal preparation formula in effervescent form with the main ingredient being African leaves. Testing of the dosage formula includes organoleptic tests, water content, pH, and dispersing time. The research results showed that one of the three formulas had better stability after 7 days of storage. After 7 days of storage, the color of the formula became lighter, the pH value changed slightly (7-8), the water content was 2.3% and the dispersion time was 2.00 minutes. This formula can be used as input for further research regarding testing its activity as an antidiabetic through inhibiting alpha-amylase in vitro.